A polarizing sheet and a method for manufacturing the same

CN121142704BActive Publication Date: 2026-10-16CHONGQING LIANGJIANG LIANCHUANG ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511501505.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2026-10-16
Estimated Expiration
2045-10-21

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明的目的在于提供一种偏光片,旨在解决现有技术中偏光片使用的三醋酸纤维素层在高温高湿的条件下易出现分层现象,而导致聚乙烯醇层边缘与水汽接触发生碘迁移,从而使得偏光片边缘功能失效的技术问题

Benefits of technology

[0006]Compared with the prior art, the beneficial effects of the present invention are as follows: by stacking high-alumina glass, epoxy resin frame and UTG encapsulation cover in sequence, a closed accommodating cavity is formed inside. A polyvinyl alcohol layer is used inside the accommodating cavity and filled and fixed with a high light transmittance OCR adhesive (OCR, optically transparent resin). By using an OCR adhesive with the same refractive index as the traditional triacetate cellulose layer to wrap both sides of the polyvinyl alcohol layer and setting it as a whole in the closed accommodating cavity, the polarizer of the present invention will not experience edge water absorption and delamination, which would lead to edge failure, even under high temperature and high humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121142704B_ABST
    Figure CN121142704B_ABST
Patent Text Reader

Abstract

The application provides a polarizing sheet and a preparation method, wherein the polarizing sheet comprises high-aluminum glass, an epoxy resin frame, a UTG packaging cover and a release film which are sequentially stacked, the high-aluminum glass and the epoxy resin frame and the UTG packaging cover enclose a closed accommodating cavity, a polyvinyl alcohol layer is arranged in the accommodating cavity, and OCR glue is arranged for packaging the polyvinyl alcohol layer in the accommodating cavity, the UTG packaging cover is provided with pressure-sensitive glue away from the high-aluminum glass, and the pressure-sensitive glue is provided with a release film for protecting the pressure-sensitive glue away from the UTG packaging cover. The polarizing sheet in the application is provided with the epoxy resin frame on one side of the high-aluminum glass to form an accommodating cavity, and the polyvinyl alcohol layer wrapped by the OCR glue is arranged in the cavity, so that the refractive index of the polarizing sheet is ensured, and the high-temperature and high-humidity resistance of the polarizing sheet is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polarizer technology, and particularly to a polarizer and its preparation method. Background Technology

[0002] Traditional polarizers typically employ a "sandwich" structure, consisting of, from top to bottom: a cellulose triacetate layer (protecting the polyvinyl alcohol layer, providing mechanical support and weather resistance), a polyvinyl alcohol layer (the core functional layer for polarization, achieving polarization through iodine / dye adsorption), a cellulose triacetate film, a pressure-sensitive adhesive layer (bonding the polarizer to the glass substrate), and a release film (a protective adhesive layer that must be peeled off before bonding). For harsh environments such as high temperature and high humidity, epoxy resin sealing rings are added to the edges of the polyvinyl alcohol layer to block water and oxygen permeation.

[0003] With the development and popularization of LCD screens, their application scenarios have also expanded. The market increasingly demands thinner and lighter LCD screens, while harsh environments such as automotive and outdoor applications place stringent requirements on polarizers for high temperature and humidity resistance, impact resistance, and long lifespan. Adding a glass cover to protect the polarizer increases the thickness of the LCD screen, which is not suitable for the demand for thinner and lighter LCD screens. Furthermore, in harsh environments such as high temperature and humidity, even with epoxy resin sealing rings added to the edges of the polyvinyl alcohol layer, the triacetyl cellulose layer of the polarizer is prone to moisture absorption under these conditions, leading to edge delamination. This causes iodine migration due to contact between the polyvinyl alcohol layer edges and moisture, resulting in malfunction of the polarizer edge function. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide a polarizer that solves the technical problem that the triacetate cellulose layer used in existing polarizers is prone to delamination under high temperature and high humidity conditions, leading to iodine migration at the edge of the polyvinyl alcohol layer upon contact with moisture, thereby causing the edge function of the polarizer to fail.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solution: A polarizer includes a high-alumina glass, an epoxy resin frame, a UTG encapsulation cap, and a release film stacked sequentially. The high-alumina glass, the epoxy resin frame, and the UTG encapsulation cap form a closed accommodating cavity. A polyvinyl alcohol layer is disposed inside the accommodating cavity, and an OCR adhesive is disposed to encapsulate the polyvinyl alcohol layer inside the accommodating cavity. A pressure-sensitive adhesive is disposed on the side of the UTG encapsulation cap away from the high-alumina glass, and a release film is disposed on the side of the pressure-sensitive adhesive away from the UTG encapsulation cap to protect the pressure-sensitive adhesive.

[0006] Compared with the prior art, the beneficial effects of the present invention are as follows: by stacking high-alumina glass, epoxy resin frame and UTG encapsulation cover in sequence, a closed accommodating cavity is formed inside. A polyvinyl alcohol layer is used inside the accommodating cavity and filled and fixed with a high light transmittance OCR adhesive (OCR, optically transparent resin). By using an OCR adhesive with the same refractive index as the traditional triacetate cellulose layer to wrap both sides of the polyvinyl alcohol layer and setting it as a whole in the closed accommodating cavity, the polarizer of the present invention will not experience edge water absorption and delamination, which would lead to edge failure, even under high temperature and high humidity conditions.

[0007] According to one aspect of the above technical solution, the epoxy resin frame is stepped, the epoxy resin frame has a first tabletop and a second tabletop that are parallel to each other, and a first connecting surface that is close to the high-alumina glass and perpendicular to the high-alumina glass. The epoxy resin frame also has a second connecting surface located between the first tabletop and the second tabletop.

[0008] According to one aspect of the above technical solution, one side of the UTG encapsulation cover abuts against the first platform.

[0009] The present invention also provides a method for preparing a polarizer, for manufacturing the above-mentioned polarizer, wherein the preparation method includes the following steps: S1. Cut the high-alumina glass to the preset size; S2. Temper the high-alumina glass; S3. The high-alumina glass is embedded in the injection mold, and room temperature epoxy resin is injected into the mold. Then it is cured and demolded, so that the epoxy resin forms a stepped epoxy resin frame on one side of the high-alumina glass. The high-alumina glass and the epoxy resin frame enclose and form an accommodating cavity. S4. Inject OCR adhesive into the accommodating cavity, level it, and pre-cure it; S5. Place the polyvinyl alcohol layer on the OCR adhesive; S6. Inject OCR adhesive into the receiving cavity again until it is higher than the receiving cavity. Then press the UTG encapsulation cap into the epoxy resin step, maintain the pressure and start UV light to allow the OCR adhesive to fully cure. S7. Adhere the pressure-sensitive adhesive to the side of the epoxy resin frame away from the high-alumina glass, and then adhere it to the other side of the pressure-sensitive adhesive through a release film.

[0010] According to one aspect of the above technical solution, in step S2, the tempering conditions include: first tempering, prepared according to a 50:50 ratio. / Stir well, then immerse the high-alumina glass in the mixture, heat evenly to 450°C for 1 hour and maintain at 450°C for 4 hours, then stop heating and cool to room temperature; for the second tempering, prepare according to a 20:28 ratio. / Stir well, then insert the high-alumina glass into the mixture, heat evenly for 1 hour to 340°C and maintain at 340°C for 2 hours, then stop heating and cool to room temperature.

[0011] According to one aspect of the above technical solution, in step S4, the leveling height is 0.02 mm, and it is pre-cured by heating on a 60°C platform for 40 seconds.

[0012] According to one aspect of the above technical solution, in step S6, the UTG is pressurized to 0.5MPa for 5s to expel the OCR adhesive that protrudes from the accommodating cavity to fill the gap between the UTG encapsulation cap and the epoxy resin frame; the pressure is reduced to 0.2MPa and held, while UV light is turned on to irradiate the OCR adhesive in the accommodating cavity for 20s to allow it to fully cure.

[0013] According to one aspect of the above technical solution, after the tempering process in step S2, the side of the high-alumina glass away from the epoxy resin frame can be functionally treated, wherein the function includes one or more of anti-glare, anti-reflection, and anti-fingerprint.

[0014] According to one aspect of the above technical solution, the preparation method further includes cutting, grinding and polishing the edges of the epoxy resin frame after the injection molding in step S3 is completed and demolded. Attached Figure Description

[0015] Figure 1 This is a cross-sectional view of the polarizer in the first embodiment of the present invention; Figure 2 This is a schematic flowchart of the polarizer preparation method in the second embodiment of the present invention; Explanation of key component symbols: 1-High-alumina glass, 2-Epoxy resin frame, 21-First platform, 22-Second platform, 23-First connecting surface, 24-Second connecting surface, 3-OCR adhesive, 4-Polyvinyl alcohol layer, 5-UTG encapsulation cap, 6-Pressure-sensitive adhesive, 7-Release film; The following detailed description, in conjunction with the accompanying drawings, will further illustrate the present invention. Detailed Implementation

[0016] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Several embodiments of the invention are illustrated in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete.

[0017] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there may be an intervening component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there may be an intervening component. The terms "vertical," "horizontal," "left," "right," and similar expressions used in this document are for illustrative purposes only.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0019] See Figure 1 The polarizer provided in the first embodiment of the present invention includes a high-alumina glass 1, an epoxy resin frame 2, and a UTG encapsulation cover 5 (UTG, ultra-thin flexible glass), which are stacked sequentially. The epoxy resin frame 2 is arranged in a stepped structure on one side of the high-alumina glass 1, surrounding its periphery. The epoxy resin frame 2 has a first platform 21 and a second platform 22 arranged parallel to one side of the high-alumina glass 1, and a first connecting surface 23 arranged close to and perpendicular to one side of the high-alumina glass 1 and a second connecting surface 24 arranged between the first platform 21 and the second platform 22. The UTG encapsulation cover 5 is bonded to the first platform 21 by OCR adhesive 3, and the sidewall of the UTG encapsulation cover 5 is also bonded to the second connecting surface 22 by OCR adhesive 3. The high-alumina glass 1, epoxy resin frame 2, and UTG encapsulation cover 5 are fixed together to form a closed accommodating cavity. The polyvinyl alcohol layer 4 is filled and fixed inside the accommodating cavity by OCR adhesive 3. This invention avoids the polarizer from failing at the edges due to contact with moisture in the environment under high temperature and high humidity conditions by wrapping the polyvinyl alcohol layer 4 in OCR adhesive 3, which has a refractive index similar to that of the traditional triacetate cellulose layer, and placing it in a closed accommodating cavity. In addition, the wrapping of the polyvinyl alcohol layer 4 with OCR adhesive 3 improves the shock resistance of the polyvinyl alcohol layer 4. Since the visible light transmittance of OCR adhesive 3 is over 98% and the UV blocking rate is 99%, it can effectively protect the polyvinyl alcohol layer 4 from damage by UV light in all directions.

[0020] A pressure-sensitive adhesive 6 is provided on the other side of the UTG encapsulation cover 5, and a release film 7 is attached to the other side of the pressure-sensitive adhesive 6 to protect one side of the pressure-sensitive adhesive 6. In use, the release film 7 is peeled off and the entire polarizer is attached to one side of the glass substrate through the pressure-sensitive adhesive 6.

[0021] See Figure 2 The second embodiment of the present invention provides a method for preparing a polarizer, the method steps of which include: S1. Cut the high-alumina glass 1 into appropriate sizes; Specifically, the high-alumina glass 1 is first cut into hexahedrons with dimensions 2mm longer and 0.1mm-0.5mm thick than the required length and width. For example, for electronic products that require thinness and lightness, the thickness is generally set to less than 0.2mm, while for automotive applications, a thickness greater than 0.4mm is beneficial for impact resistance. It is understood that those skilled in the art can choose the thickness according to the actual situation.

[0022] S2. Temper the high-alumina glass 1; The first tempering treatment conditions were as follows: a 50:50 mixture was prepared in an environment with an ambient temperature of 20-26℃. / Mix the glass, then immerse the cut high-alumina glass 1 completely in the mixture, heat it evenly for 1 hour to 450°C, maintain the temperature at 450°C for 4 hours, stop heating and cool to room temperature; Second tempering conditions: Prepare a 20:80 mixture at an ambient temperature of 20-26℃. / The mixture is prepared by immersing the cut high-alumina glass 1 completely into the mixture and heating it uniformly to 340°C for 1 hour. The temperature is then maintained at 340°C for 2 hours. Heating is then stopped and the glass is cooled to room temperature. After tempering, the high-alumina glass 1 has a surface compressive stress CS ≥ 700 MPa, a stress layer depth DOL ≥ 15 μm, and a central tensile stress CT ≤ 25 MPa. It is understandable that the tempering process makes the high-alumina glass 1 stronger and harder, which allows it to replace the traditional glass cover plate and OCA adhesive layer structure, thereby reducing the overall thickness of the polarizer.

[0023] S3. The high-alumina glass 1 is embedded in the injection mold, and room temperature epoxy resin is injected into the mold. Then it is cured and demolded. The epoxy resin forms a stepped epoxy resin frame 2 on one side of the high-alumina glass 1. The high-alumina glass 1 and the epoxy resin frame 2 enclose and form an accommodating cavity. Specifically, the tempered high-alumina glass 1 is installed and embedded into a pre-designed injection mold. Epoxy resin is injected at room temperature, and then the entire assembly is placed in an oven at 150°C for 2 hours. After complete curing, it is demolded, thus forming an epoxy resin frame 2 on one side of the high-alumina glass 1. It should be noted that the curing of epoxy resin can be divided into heat curing and cold curing. The epoxy resin curing in this embodiment is heat curing. The curing agent added to the epoxy resin can be any one of acid anhydride, aromatic amine, dicyandiamide, etc. The epoxy resin frame 2 formed under these heat curing conditions can resist the softening and deformation phenomenon in high-temperature and high-humidity environments such as automotive environments.

[0024] In this embodiment, the epoxy resin frame 2 is bonded in a stepped shape around one side of the high-alumina glass 1, and the middle of the frame and the other side of the high-alumina glass 1 form a cavity.

[0025] It is worth mentioning that during the actual injection molding process, the edges of the epoxy resin frame 2 formed after demolding are not regular enough, and it is necessary to cut, grind and polish the edge waste.

[0026] S4. Inject OCR adhesive 3 into the accommodating cavity. After leveling, the height is 0.02mm. Then, pre-cure the adhesive by heating it at 60°C on the platform for 40 seconds.

[0027] S5. Place the polyvinyl alcohol layer 4 on the pre-cured OCR adhesive 3. It can be understood that the pre-cured OCR adhesive 3 forms a pre-gel state that is a transitional state between liquid and solid. Specifically, the surface loses its fluidity, thus providing sufficient support for the polyvinyl alcohol layer 4. S6. Inject OCR adhesive 3 into the cavity again until it is slightly higher than the cavity. Then press the UTG encapsulation cap 5 into the epoxy resin step, maintain a certain pressure and start UV light to completely cure OCR adhesive 3. Specifically, OCR adhesive 3 is injected again into the accommodating cavity, filling the entire cavity and slightly protruding above the first platform 21. Then, the UTG encapsulation cap 5 is pressed into the epoxy resin frame 2. It should be noted that the dimensions of the UTG encapsulation cap 5 are the same as the dimensions enclosed by the second connecting surface 24 of the epoxy resin, and its thickness is the same as the height of the second connecting surface 24. Therefore, during the pressing of the UTG encapsulation cap 5 into the epoxy resin frame 2, the protruding OCR adhesive 3 will be squeezed and filled into the gap between the first platform 21 and the UTG encapsulation cap 5 and the epoxy resin frame 2. During the pressing process, the pressure is set at 0.5 MPa and lasts for 5 seconds until the UTG encapsulation cap 5 abuts against the first platform 21. Then, the pressure is reduced to 0.2 MPa, and UV light is turned on. The light conditions are: UV wavelength of 365 nm and energy of 3000 mJ / cm². 2The process takes 20 seconds, during which the OCR adhesive 3 is irradiated to fully cure. It's worth noting that in this embodiment, the size of the polyvinyl alcohol layer 4 is slightly smaller than the size of the accommodating cavity. After the OCR adhesive 3 is fully cured, the polyvinyl alcohol layer 4 is completely encased within it. Under the seal of the UTG encapsulation cap 5, the polyvinyl alcohol layer 4 is situated within a closed accommodating cavity. The epoxy resin frame 2 forms the accommodating cavity, and the OCR adhesive 3 provides dual protection for the polyvinyl alcohol layer 4. This prevents the polarizer from delaminating at the edges under high temperature and humidity conditions, thus preventing moisture from entering and contacting the polyvinyl alcohol layer 4, causing polarizer failure. Furthermore, since the refractive index of the OCR adhesive 3 is 1.5, while the refractive index of the traditional triacetate cellulose layer is 1.56, the refractive index of the polyvinyl alcohol layer 4 is 1.49, and the refractive index of the high-alumina glass 1 and the UTG encapsulation cap 5 is 1.53, according to the reflectance formula... In this context, n1 and n2 represent light incident from a medium with refractive index n1 to a medium with refractive index n2. Since the refractive index of the OCR adhesive 3 is similar to that of the cellulose triacetate layer, using OCR adhesive 3 instead of the traditional cellulose triacetate layer not only avoids the edge separation problem caused by water absorption in the cellulose triacetate layer under high temperature and humidity conditions, but also, according to the reflection formula, the reflectivity of the liquid crystal display screen using the polarizer of this invention is lower than that using a traditional polarizer, thus improving the transmittance of the polarizer. Therefore, the polarizer liquid crystal display screen of this invention reflects less ambient light into the human eye, increases brightness, and results in a clearer and more transparent display.

[0028] S7. Adhere the pressure-sensitive adhesive 6 to the side of the epoxy resin frame 2 away from the high-alumina glass 1, and attach the pressure-sensitive adhesive 6 to the other side of the pressure-sensitive adhesive 6 through the release film 7 to protect the pressure-sensitive adhesive 6.

[0029] In some embodiments, after the tempering process in step S2, the side of the high-alumina glass 1 away from the epoxy resin frame 2 can be functionally treated, such as one or more of anti-glare, anti-reflection, and anti-fingerprint. The functional treatment process can be one or more of chemical etching, spraying, and coating, depending on different requirements.

[0030] In summary, the polarizer in the above embodiments of the present invention, by selecting high-alumina glass and tempering it, improves the structural strength and hardness of the high-alumina glass, and reduces the thickness of the polarizer compared to the traditional cover glass and OCA (Optically Transparent Acrylic Acid) layer structure. An epoxy resin frame and a TUG encapsulation cap are stacked on one side of the high-alumina glass to form a closed accommodating cavity. A polyvinyl alcohol layer wrapped with OCR adhesive is placed within the accommodating cavity, improving the polarizer's resistance to high temperature and humidity. Simultaneously, by replacing the traditional triacetate cellulose layer with OCR adhesive, the polarizer of the present invention has better light transmittance, resulting in a clearer and more transparent display screen.

[0031] In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0032] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the appended claims.

Claims

1. A method for preparing a polarizer, characterized in that, The preparation method includes the following steps: S1. Cut the high-alumina glass to the preset size; S2. Temper the high-alumina glass; S3. The high-alumina glass is embedded in the injection mold, and room temperature epoxy resin is injected into the mold. Then it is cured and demolded, so that the epoxy resin forms a stepped epoxy resin frame on one side of the high-alumina glass. The high-alumina glass and the epoxy resin frame enclose and form an accommodating cavity. S4. Inject OCR adhesive into the accommodating cavity, level it, and pre-cure it; S5. Place the polyvinyl alcohol layer on the OCR adhesive; S6. Inject OCR adhesive into the receiving cavity again until it is higher than the receiving cavity. Then press the UTG encapsulation cap into the epoxy resin step, maintain the pressure and start UV light to allow the OCR adhesive to fully cure. S7. Adhere the pressure-sensitive adhesive to the side of the epoxy resin frame away from the high-alumina glass, and then adhere it to the other side of the pressure-sensitive adhesive through a release film.

2. The preparation method according to claim 1, characterized in that, In step S2, the tempering conditions include: first tempering, KNO3 / NaNO3 is prepared in a 50:50 ratio and stirred evenly, then the high-alumina glass is inserted into the mixture, heated evenly for 1 hour to 450°C and maintained at 450°C for 4 hours, then heating is stopped and cooled to room temperature; second tempering, KNO3 / NaNO3 is prepared in a 20:28 ratio and stirred evenly, then the high-alumina glass is inserted into the mixture, heated evenly for 1 hour to 340°C and maintained at 340°C for 2 hours, then heating is stopped and cooled to room temperature.

3. The preparation method according to claim 1, characterized in that, In step S4, the leveling height is 0.02 mm, and the surface is pre-cured by heating on a 60°C platform for 40 seconds.

4. The preparation method according to claim 1, characterized in that, In step S6, the UTG is pressurized to 0.5 MPa for 5 seconds to expel the OCR adhesive that protrudes from the accommodating cavity to fill the gap between the UTG encapsulation cap and the epoxy resin frame; the pressure is then reduced to 0.2 MPa and maintained, while UV light is simultaneously turned on to irradiate the OCR adhesive in the accommodating cavity for 20 seconds to allow it to fully cure.

5. The preparation method according to claim 1, characterized in that, After the tempering process in step S2, the side of the high-alumina glass away from the epoxy resin frame is subjected to functional treatment, wherein the function includes one or more of anti-glare, anti-reflection, and anti-fingerprint.

6. The preparation method according to claim 1, characterized in that, The preparation method further includes cutting, grinding and polishing the edges of the epoxy resin frame after the injection molding in step S3 is completed and the mold is demolded.

Citation Information

Patent Citations

  • Method and structure improving reliability of optical membrane assembly

    CN106646687A

  • Polarizer, display panel and electronic equipment

    CN212781318U